Pelayanan Jasa Keperawatan: Tingkat Kepuasan Pasien pada Unit Rawat Inap Rumah Sakit Umum “dr. Slamet” Garut - Lindayani Lindayani (Entrepreneurship Faculty, Universitas Garut, 2019)
The present study looks at in-patient nursing service at Garut Regional Public Hospital dr. Slamet and patient satisfaction as viewed from the gap between service performance and patient expectations. Using a descriptive approach, the influence of in-patient nursing service on patient satisfaction was analyzed. Research data were collected through observation and questionnaires addressed to the patients. The results of the study lead to a conclusion that patients were satisfied with the in-patient nursing care they received. It is suggested that the hospital improve their responsiveness to patient complaints, provide information in simple and easy to understand language, improve the skills of medical personnel by providing regular education and training, improve patient safety and trust, improve service personnel skills such as knowledge in using disease diagnostic tools, hospitality skills, and communication skills.